Effect of supplementation of fish meal on growth and reproductive performance of crossbred heifers (Journal of the Bangladesh Agricultural University, 2013)
The experiment was conducted at Bangladesh Agricultural University Dairy Farm to study the effect of fish meal (FM) on growth and reproductive performances of crossbred heifers. The experiment was designed into four treatment (T0=0% FM; T1=5% FM; T2=7.5% FM and T3 =10% FM) groups having initial weight 231.33 ± 32.39, 241.00 ± 46.29, 198.66 ±58.53 and 236.66 ± 31.64 kg, respectively. The average age of the animal is 2 years 9 month. Results of the experiment revealed that there was a significant difference of FM on daily DMI (kg/d). In 90 days period, FM with rice straw based diet had significant effect on daily weight gain (kg/d) of crossbred heifers. DM, CP and CF digestibility (%) differ significantly (p